Bank entry, competition, and the market for corporate securities underwriting - Gande, A (Journal of Financial Economics, 1999)
This paper examines the competitive effects of commercial bank entry into the corporate debt underwriting market, particularly with respect to underwriter spreads, ex-ante yields, and market concentration. We find that underwriter spreads and ex-ante yields have declined significantly with bank entry, consistent with the market becoming more competitive. This effect is strongest among the lower-rated and smaller debt issues of which banks have underwritten a relatively greater share. The early evidence also indicates that bank entry has tended to decrease market concentration. Overall, our results suggest that bank entry has had a pro-competitive effect.